1976
DOI: 10.1136/bmj.1.6008.490
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic allergic alveolitis in Scottish maltworkers.

Abstract: W BLYTH, BSC, PHD, lecturer it was usually caused by a type 3 allergic reaction to Aspergillus clavatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…Those exposed to conidia ran a three times greater risk of symptoms of hypersensitivity pneumonitis. This evidence corroborates the work of Portuguese authors (1)(2)(3) who found that the inhalation of P frequentans reproduced symptoms of suberosis and that exposure to conidia implies a risk of hypersensitivity pneumonitis (41,42). Those workers with symptoms of hypersensitivity pneumonitis and fever , the latter persistent with exposure to conidia, also had precipitins to P frequentans and restrictive ventilatory impairment, which ruled out the organic dust toxic syndrome (43).…”
Section: Discussionsupporting
confidence: 79%
“…Those exposed to conidia ran a three times greater risk of symptoms of hypersensitivity pneumonitis. This evidence corroborates the work of Portuguese authors (1)(2)(3) who found that the inhalation of P frequentans reproduced symptoms of suberosis and that exposure to conidia implies a risk of hypersensitivity pneumonitis (41,42). Those workers with symptoms of hypersensitivity pneumonitis and fever , the latter persistent with exposure to conidia, also had precipitins to P frequentans and restrictive ventilatory impairment, which ruled out the organic dust toxic syndrome (43).…”
Section: Discussionsupporting
confidence: 79%
“…Although these more modem systems speed up the process, the high level of moisture availability and the presence of solubilised and partially solubilised nutrients still favour microbial growth, although less so than floor malting (Flannigan et al, 1982). As far as malt worker's lung is concemed, Grant et al, (1976) concluded from a survey of Scottish maltings that the incidence of the disease would dimini sh with mechanisation. The survey revealed that 5.2% of all workers were affected by the disease, with almost as many workers in box maltings (6.2%) as in floor maltings (6.8%) having the disease, but where enclosed systems had been installed only 1.1% (Grant et al, 1976).…”
Section: A Clavatus As Arespiratory Hazardmentioning
confidence: 99%
“…As far as malt worker's lung is concemed, Grant et al, (1976) concluded from a survey of Scottish maltings that the incidence of the disease would dimini sh with mechanisation. The survey revealed that 5.2% of all workers were affected by the disease, with almost as many workers in box maltings (6.2%) as in floor maltings (6.8%) having the disease, but where enclosed systems had been installed only 1.1% (Grant et al, 1976). However, as more recent reports show, floor malting systems are still in use and play host to A. clavatus (Rabie and Lübben, 1984;Shlosberg et al, 1991).…”
Section: A Clavatus As Arespiratory Hazardmentioning
confidence: 99%
“…These were tested in accordance with the ASTM G21, JIS Z 2911, and ATCC test method [30]. These fungi were either pathogens causing liver cancer, diseases of the genitalia, or which induced bronchitis, allergies and asthma in humans or which degraded cellulosic materials, paper, leather, and wood products [14][15][16]. Among the fungi tested, the growth of A. clavatus, A. niger, Cl.…”
mentioning
confidence: 99%